Genetic programming theory and practice - Riolo Rick; Worzel Bill (Boston Kluwer Academic, 2003)
This book explores the emerging interaction between theory and practice in the cutting-edge, machine learning method of Genetic Programming (GP). Chapters include such topics as John Koza's development of human-competitive electronic circuit designs; Dav
Keywords: Genetic programming(Computer science)